Development Of A Phototherapy Equipment For Neonatal Jaundice, Based On An Algorithm Of Treatment And A Predictive Method For Detection Of The Bilirubin Level - Morales-Licla, Pedro (2016)
Since the efficacy of phototherapy has been demonstrated, it has become the main method for the prevention and treatmentof hyperbilirubinemia in the neonate with neonatal jaundice. Therefore, the objective of this project is to decrease the abnormallevel of bilirubin in the blood with innovation tools and to place it at low risk levels. For this, the proposed design consists ofa blue light source, which offers a uniform light distribution throughout the neonate’s surface; A control system that ensuresthe level of constant irradiance throughout the treatment, a noninvasive predictive method to determine the level of bilirubinin the neonate and a programmable interface that allows to suggest the most effective type of treatment. Electrical hazardsaccording to IEC 60601-1 standard for medical equipment are included.